0175 Development of a tonsil-tie training simulator. (2nd November 2015) - Nicklin, Jane; Lakin, Sandra; Carr, Kelly
Abstract : Context: Tonsillectomy is one of the most common procedures that need to be accomplished in the early stages of a trainee's career. The key message from the National Prospective Tonsillectomy Audit was that cold steel dissection combined with ligation for haemostasis reduced the number of postoperative haemorrhages. Despite this recommendation and the development of several improvised home-made simulators using cups, tissue boxes and running trainers, there is still no real opportunity through realistic simulated practice for trainees to demonstrate the manual dexterity and spatial orientation necessary to gain the operative skill of tonsil haemostasis using ligation. Description of innovation: Following a short scoping exercise of the current simulators available, several redundant dental phantom head with table-fittings were acquired and engineered to enable maximum extension of the head and neck, and sufficient opening of the jaw to insert the Boyle-Davis gag. An old Laerdal Airway manikin's throat assembly was used for measurements and initial mouldings and casts and a silicone insert was fabricated to reproduce the mouth and oropharynx. Silicone pull-through laces were pushed through each of the tonsillar fossae replicating tonsil remnants/bleeding points to facilitate ligation using ties. Outcomes: Despite the restricted testing and validation due to the unveiling and use in the clinical skills station at ENT Speciality National Recruitment in early 2015, the overall evaluation was excellent; particularly at it had the added value of demonstrating additional relevant skills i.e. setting-up the Boyle-Davis gag, insertion with a RAE tube in-situ, using a headlight and selecting appropriate tonsillectomy instrumentation. The product design is to be registered and early discussions are taking place with one of the leading part-task trainer manufacturers. References: Lowe D, van der Meulen J, Cromwell D, et al . Key messages from the National Prospective Tonsillectomy Audit. Laryngoscope 2007;117:717–724 Al-Hussaini A, Addams-Williams J, Tomkinson A. The cardiff cup – a model for tonsillectomy tie training. Otolaryngology 2011;1(1) Raja MK, Haneefa MA, Chidambaram A. Yorick's skull model for tonsillectomy tie training. Clin Otolaryngol 2008;33:187–188